Conservation of the abscission signaling peptide IDA during Angiosperm evolution: withstanding genome duplications and gain and loss of the receptors HAE/HSL2 - Stø, Ida M.; Orr, Russell J. S.; Fooyontphanich, Kim; Jin, Xu; Knutsen, Jonfinn M. B.; Fischer, Urs; Tranbarger, Timothy J.; Nordal, Inger; Aalen, Reidunn B. (Frontiers in Plant Science, 2015)
The peptide INFLORESCENCE DEFICIENT IN ABSCISSION (IDA), which signals through the leucine-rich repeat receptor-like kinases HAESA (HAE) and HAESA-LIKE2 (HSL2), controls different cell separation events in Arabidopsis thaliana. We hypothesize the involvement of this signaling module in abscission processes in other plant species even though they may shed other organs than A. thaliana. As the first step towards testing this hypothesis from an evolutionarily perspective we have identified genes encoding putative orthologues of IDA and its receptors by BLAST searches of publically available protein, nucleotide and genome databases for angiosperms. Genes encoding IDA or IDA-LIKE (IDL) peptides and HSL proteins were found in all investigated species, which were selected as to represent each angiosperm order with available genomic sequences. The 12 amino acids representing the bioactive peptide in A. thaliana have virtually been unchanged throughout the evolution of the angiosperms; however, the number of IDL and HSL genes varies between different orders and species. The phylogenetic analyses suggest that IDA, HSL2 and the related HSL1 gene, were present in the species that gave rise to the angiosperms. HAE has arisen from HSL1 after a genome duplication that took place after the monocot - eudicots split. HSL1 has also independently been duplicated in the monocots, while HSL2 has been lost in gingers (Zingiberales) and grasses (Poales). IDA has been duplicated in eudicots to give rise to functionally divergent IDL peptides. We postulate that the high number of IDL homologs present in the core eudicots is a result of multiple whole genome duplications. We substantiate the involvement of IDA and HAE/HSL2 homologs in abscission by providing gene expression data of different organ separation events from various species.